The interpreter as traitor: Multilingualism in Guizi lai le (Devils on the Doorstep) - Takeda, Kayoko (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
This paper discusses ways in which multilingualism is represented in an award-winning Chinese film, Guizi lai le, and its subtitling. Known as Devils on the Doorstep in English, the movie approaches its multilingual setting realistically: Chinese villagers speak in Chinese, Japanese soldiers in Japanese, and interpreters mediate their communication. In examining the Chinese, Japanese and English subtitles of the film, the study focuses on the different strategies used by the translators to represent multilingualism and to subtitle offensive language. The behavior and fate of the Chinese interpreter in the film is also explored, with special attention to the power interpreters possess for controlling and manipulating information and the notion of the interpreter as traitor and war criminal in the context of conflict. Findings of this research invite further investigation into how the audience views multilingualism in cinema and how the identity and loyalty of interpreters is depicted in war-themed movies. Collaborative work by researchers from different language and cultural backgrounds should also be encouraged.